PENGARUH INSECURE TERHADAP INTERAKSI SOSIAL PADA SANTRI BABUN NAJAH - Jumi Adela Wardiansyah (AflahConsilia : Jurnal Bimbingan dan Konseling, 2022)
The success of a learning process is closely related to the interaction process. Islamic boarding school, an ustadz/ustazah besides being a teacher must be an uswah/examples in instilling religious values ​​and moral values. In addition, the interaction between the ustadz/ustazah and the santri is expected to provide understanding to the students including cognitive, affective and psychomotor abilities. This study uses a qualitative type of research with the type of field research with the aim of providing an overview of the form of social interaction. qualitative approach with the type of case study, using data collection techniques of observation, interviews, and documentation. Data analysis in this study uses data condensation, data display, and verification. The results of this study indicate that. 1). Lack of self-confidence because of feelings of insecurity and discomfort towards him. People who lack self-confidence can feel anxious, ashamed and afraid of their own inadequacy. Situations like this can make students depressed excessively so that it triggers a mental disorder. 2). Lack of self-confidence factors such as not accepting one's own abilities. Still see the advantages of others compared to himself. An individual effort process to obtain a new behavior change as a whole, as a result of the experience itself there must be a process of interaction with the environment. These changes will be expressed in all aspects of cognitive, affective and psychomotor. 3). His role as a hostel builder is due to the lack of self-confidence of students due to the lack of independence of students in attitude or in making decisions, most of the students here become insecure of themselves and compare themselves with their friends.